Erosi dan Sedimentasi Akibat Perubahan Tata Guna Lahan pada DAS Winongo Menggunakan Metode USLE dan Aplikasi Arcgis (Erosion and Sedimentation Caused by Land Use Changes in The Winongo Watershed Using USLE Method and The ArcGIS Application) - Surya Lesmana; Bunsa Jondan Satriawan; Jazaul Ikhsan (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2024)
Erosion is one of the most important things in watershed management, and is influenced by various natural and non-natural factors. Natural factors that affect erosion are: rain, soil type, slope length, and slope gradient. Land use is a non-natural factor that is influenced by various human activities. It is an important factor in calculating erosion that occurs in a watershed. The purpose of this study was to analyze (1) land use changes in the Winongo watershed, (2) erosion rate that occurs due to land use changes in the Winongo watershed, (3) the dynamics erosion classification changes in the Winongo watershed in 2001-2021 and (4) sedimentation that occurs in the Winongo watershed. The results of the study found a change in CP value from 0.61 to 0.65 which means that there was a change in land use in the Winongo watershed. An erosion rate of 22.78 tons/ha/year is classified as light erosion classification. During 2001-2021, areas with moderate, severe, and very severe erosion hazard classifications increased by 0.4% or 983.1 ha. The average of sediment produced in the Winongo watershed is 121,398.69 tons/year.